Maternal Factors in Pregnancy and Ethnicity Influence Childhood Adiposity, Cardiac Structure, and Function - Sophia Khan; Andrew Whatmore; Reena Perchard; Aysha Khan; Avni Vyas; Jaspal Dua; J. Kennedy Cruickshank; Peter Clayton (Frontiers Media S.A., 2022)
ImportanceThe links between maternal and offspring adiposity and metabolic status are well established. There is much less evidence for the impact of these relationships combined with ethnic background on cardiac structure and function in childhood.ObjectiveTo test the hypothesis that ethnicity, maternal adiposity and glycemic status, and child adiposity affect cardiac structure and function.DesignA prospective cohort study.SettingA single-center mother-child cohort study. The cohort is a subset of the international multi-center Hyperglycemia and Adverse Pregnancy Outcomes (HAPO) study.ParticipantsThis study included 101 healthy pre-pubertal British-born children [56 White Europeans (WEs) and 45 South Asians (SAs)] with a median age of 9.1 years, range 6.0-12.2 years, at the time of the investigation.Main Outcomes and MeasuresAnthropometric and echocardiographic measurements were made on the cohort. Maternal pregnancy and birth data were available. Relationships between maternal parameters (BMI and glucose status), child adiposity, and echo measures were assessed.ResultsDespite no ethnic difference in BMI SDS at a median age of 9.1 years, SA children exhibited higher levels of body fat than WE children (whole body, right arm, and truncal fat all p < 0.001). SA children also exhibited greater changes in weight and height SDS but not BMI SDS from birth than WE children. As expected, maternal BMI correlated with child BMI (r = 0.28; p = 0.006), and body fat measures (e.g., whole body fat r = 0.25; p = 0.03). Maternal fasting glucose levels were associated with child body fat measures (r = 0.22-0.28; p = 0.02-0.05). Left ventricular (LV) indices were not different between SA and WE children, but E/A and E'/A' (measures of diastolic function) were lower in SA when compared with WE children. LV indices correlated positively to BMI SDS and body fat markers only in SA children. Maternal fasting and 2-h glucose were negatively correlated with E'/A' in SA children (r = −0.53, p = 0.015, and r = −0.49, p = 0.023, respectively) but not in WE children.Conclusion and RelevanceSA and WE children exhibit differences in adiposity and diastolic function at a median age of 9.1 years. Novel relationships between maternal glycemia, child adiposity, and cardiac structure and function, present only in SA children, were identified.